Book Reviews - Masierek, Edyta; Pielesiak, Iwona (European Spatial Research and Policy, 2022)
"Final report – Innovative strategies for retail revitalisation in medium-sized cities" Urbact/RetaiLink, 2018, 170 pages, Christa REICHER, Fabio BAIRO-KAISER, Päivi KATAIKKO-GRIGOLEIT, Sarah MÜLLER, Jan POLÍVKA (eds), Urban Integration. From Walled City To Integrated City, Stadt- und Raumplanung, vol. 19, Zürich: LIT, 2019, 100 pages